1,12-cyclic-apelin-12 counters vascular smooth muscle cell proliferation and atherosclerosis through inhibiting aerobic glycolysis - Ruirui Lu; Xiaosi Zhou; Huimei Liu; Sisi Fan; Xiaohui Huang; Fengting Guo; Bin Huang; Linxi Chen; Lanfang Li (Toxicology and Applied Pharmacology, 2026)

Cold plasma treatment enhanced defense responses against gray mold and enhances postharvest quality in cherry tomatoes - Miaomiao Ge; Ruirui Qiu; Xinzhi Fang; Ling Li; Jian Guo (Food Research International, 2026)

Mg/Ca ratio-regulated phase differentiation of microbially derived CaCO3 and its effects on Cu2+, Cd2+, and Pb2+ immobilization - Kaiming Hu; Yanyang Zhao; Yishui Han; Zuozhen Han; Ruirui Meng; Xiao Gao; Jie Li; Na Guo (Journal of Hazardous Materials, 2026)

Achieving 96.6% energy-storage efficiency in Nd-doped tungsten-bronze ceramics through A-site vacancy engineering - Zhihong Wang; Yangfei Gao; Bian Yang; Mei Bai; Xiangran Pei; Hai Ci; Ruirui Kang; Junbo Xu; Yingying Zhao; Mengyao Guo; Fei Li; Xiaojie Lou (Chemical Engineering Journal, 2026)

Historical grazing intensity determines the response patterns of plant community and soil nutrient stocks to grazing exclusion in a temperate meadow steppe - Haonan Guo; Xiaoping Xin; Jiquan Chen; Phil J. Murray; Maira Kussainova; Wei Fang; Zhigang Zhao; Hui Li; Cuixia Jiang; Yufan Si; Amarjargal Amartuvshin; Alim Pulatov; et al. (Agriculture, Ecosystems & Environment, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

Novel mutation sites in yeast FAS enhance the production of C6–C10 fatty acids and their ethyl esters - Yupeng Wang; Junbao Gong; Xinyu Lu; Yanfang Chen; Ruirui Li; Ying Guo; Chunhong Sun; Xinjian Wang; Ying Zhou; Xiaole Wu; Yefu Chen (Food Bioscience, 2026)

Anaerobic digestion of acidic waste mash via light-assisted & hemin-acclimated inoculum: A case study of cassava alcohol stillage - Yang Wang; Dong Guo; Junlin Ji; Zhihan Luo; Zhicheng Zhu; Ruirui Hou; Kai Wu; Hong Yang; Jinhe Jiang; Fang Yin (Biomass and Bioenergy, 2026)

Deep learning based behavioural monitoring and analysis of grazing sheep - Tianci Hu; Jinxing Li; Ruirui Yan; George Vlontzos; Wenxin Zheng; Xinwen Chen; Leifeng Guo (Biosystems Engineering, 2026)

Nationwide occurrence, profiles, and health risks of legacy and emerging per- and polyfluoroalkyl substances (PFAS) in tap water across China - Chuanming Zhao; Qingwei Guo; Ruirui Zhang (Environmental Pollution, 2026)

Ergothioneine and lactoferrin exert synergistic neuroprotective effects through the Tnfrsf12a/NF-κB signaling axis - Hui Li; Xiaoyu Wang; Yujie Xu; Zhibao Cheng; Ruirui Li; Jingyuan Xiong; Guo Cheng (Food Bioscience, 2026)

Discovery of juglone derivatives as potential nematicides by exacerbating oxidative damage - Xue Guo; Ruirui Zhao; Jie Wang; Yan Li; Xiuhai Gan (Pesticide Biochemistry and Physiology, 2026)

Enhancement of calcium oxide on hydrogen production and degradation of polylactic acid microplastics in anaerobic fermentation - Xiaoxuan Zhu; Ruirui Shang; Xi Yang; Chuanzheng Song; Hui Mu; Chunhui Zhao; Huanhuan Guo; Yongfang Zhang (Journal of Environmental Management, 2026)

Rewiring (p)ppGpp metabolism for high-yield anaerobic methanol and CO2 conversion in Butyribacterium methylotrophicum - Yuanke Guo; Feiyi Zhuang; Rui Zhang; Ruirui Qin; Jiao Feng; Kequan Chen; Xin Wang (Chemical Engineering Journal, 2026)

N-halamine-grafted MIL-125-NH2(Ti) as a long-lasting chlorine reservoir for round-the-clock decontamination of Aspergillus aerosols - Ruirui Hou; Hao Yang; Fengming Hou; Yihang Li; Zhipeng Guo; Jin Li; Wei Wei; Ang Wei (Chemical Engineering Journal, 2026)

Decoupling effects of driving factors on sediment load in the middle reaches of the Yellow River - Chaohui Ma; Xiaoxue Guo; Ruirui Xu; Peng Gao; Jiahui Zhou; Yuxuan Zhang; Xingmin Mu (CATENA, 2026)

Biomineralization induced by Shigella dysenteriae JS3: The mechanism, and the differences between biotic and abiotic whewellite and struvite - Na Guo; Jizheng Qiao; Shuhua Zhang; Shengzhe Gao; Yanhong Zhao; Chao Han; Hui Zhao; Yanyang Zhao; Xiao Gao; Ruirui Meng; Bin Cao; Yu Li; et al. (Chemical Geology, 2026)

Functionalization of Mn2+ with Zr-MOF for ratiometric fluorescent and smartphone-integrated colorimetric detection of hydrogen peroxide - Xiaojing Chai; Ruirui Zhao; Muhammad Asif; Ayesha Aziz; Chuan Dong; Youhong Tang; Shaomin Shuang; Yujing Guo (Chemical Engineering Journal, 2026)

Changes in plant community composition and soil resource drive jointly fine root productivity response to grazing in a meadow steppe - Hui Li; Changliang Shao; Yuguang Ke; Xiaoping Xin; Ziwei Tao; Yufan Si; Haonan Guo; Cuixia Jiang; Ruirui Yan; Guozhen Du; Zihao Li; Feng Liu (Plant and Soil, 2026)

Corrigendum to “Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region” [Sci. Total Environ. 946 (2024) 174054] - Xiaoping Xin; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; Ruirui Yan; et al. (Science of The Total Environment, 2025)

Cation engineering enables visible tunable tricolor long persistent luminescence in Cu2+-activated phosphors for advanced information encryption - Xingyang Peng; Rongmao Li; Yanzhi Zhang; Hao Guo; Kang Wang; Can Yuan; Xiang Guo; Chaoyong Deng; Ruirui Cui (Chemical Engineering Journal, 2025)

National-scale genomic diagnosis of rare diseases in China - Xiaodong Luan; Ye Jin; Liping Guan; Peng Liu; Hailong Feng; Dingding Zhang; Jingdan Chen; Weida Liu; Fangyuan Li; Anqi Wang; Kun Zhao; Ruirui He; et al. (Science Bulletin, 2025)

Diversity-oriented optimization of 1,2,4-oxadiazole pharmacophore for the discovery of nematicides - Yuqin Ou; Qi Zhang; Xue Guo; Ruirui Zhao; Jixiang Chen; Xiuhai Gan (Molecular Diversity, 2025)

Muti-network active aerogel based on PVA, bacterial cellulose, and sodium alginate: Characterization, kinetics studies, and application for mutton preservation - Xi Zhou; Fangqu Wang; Yang Yu; Ruirui Guo; Xinran You; Xiaomei Xiang; Xiaojing Fan; Yabin Niu; Xuejiao Wang; Xianchao Feng; Lin Chen (Food Hydrocolloids, 2025)

Shedding light on the shadows: Transparency challenge in background life cycle inventory data - Jing Guo; Ruiqiao Li; Ruirui Zhang; Jianchuan Qi; Nan Li; Changqing Xu; Anthony S. F. Chiu; Yutao Wang; Hiroki Tanikawa; Ming Xu (Journal of Industrial Ecology, 2025)
Life cycle assessment (LCA) hinges on the transparency and reliability of inventory data. However, the transparency of background life cycle inventory (LCI) data sources remains unexamined. This research assesses data transparency in mainstream LCI databases using a two‐step examination system based on source findability and accessibility. Six major databases (ecoinvent, GaBi, U.S. Life Cycle Inventory Database, European Life Cycle Database, Inventory Database for Environmental Analysis, and Chinese Life Cycle Database) were analyzed by sampling processes and tracing their sources. The results reveal widespread transparency issues, with only 40%–60% of sampled processes having findable sources and <5% being fully accessible in certain databases. Incomplete documentation and complex cross‐referencing between processes and sources posed key barriers. The lack of transparency undermines LCA credibility and necessitates reconstructing databases for enhanced traceability. Although a preliminary study, these findings highlight the challenge of data transparency and provide a methodology to evaluate databases. This drives collective action to uphold transparency standards, restoring trust in LCA as a sustainability decision‐making tool.

The dynamics impact of phlorizin on gut microbiota and metabolites in an in vitro fermentation model - Dingzuo Ge; Luyao Zheng; Li Liu; Xin Chen; Jiawei Zhou; Han Ge; Liqiang Guo; Hua Hua; Ruirui Wang; Lei Zhang (Food Research International, 2025)

Warmer summers have the potential to affect food security by increasing the prevalence and activity of Actinobacteria - Yuanyuan Bao; Jan Dolfing; Zhiying Guo; Jie Liu; Xianzhang Pan; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Lixia Zhang; Ruirui Chen; Xin Li; Youzhi Feng (European Journal of Soil Biology, 2025)

A 2D/3D hierarchical hybrid enables energy-saving hydrogen production coupled with glycerol and urea electro-oxidation - Ziyu Zhou; Fenghua Ge; Ruirui Xu; Xu Dong; Mengjiao Guo; Guanwei Cui; Qian Wang; Pin Hao (Journal of Environmental Chemical Engineering, 2024)

Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region - Xiaoping Xin; Xueqi Lan; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; et al. (Science of The Total Environment, 2024)

Zirconium‑cerium modified polyvinyl alcohol/NaCMC biocomposite film: Synthesis of films through high-speed shear assisted technique and removal fluoride from water - Ruirui Yang; Fuqing Bai; Liping Mei; Wei Guo; Huanhuan Qiao; Guijie Chen; Junsheng Liu; Fei Ke; Chuanyi Peng; Ruyan Hou; Xiaochun Wan; Huimei Cai (Carbohydrate Polymers, 2024)

Behavior classification and spatiotemporal analysis of grazing sheep using deep learning - Zhongming Jin; Hang Shu; Tianci Hu; Chengxiang Jiang; Ruirui Yan; Jingwei Qi; Wensheng Wang; Leifeng Guo (Computers and Electronics in Agriculture, 2024)

Dissolved Mn2+ promotes microbially-catalyzed protodolomite precipitation in brackish oxidized water - Zuozhen Han; Jie Li; Yanyang Zhao; Qingyuan Chen; Xiao Gao; Kaiming Hu; Na Guo; Xiangyu Wei; Ruirui Meng; Chenlin Zhu; Maurice E. Tucker; Chao Han (Chemical Geology, 2024)

Design of a dual-mode ratiometric fluorescent probe via MOF-on-MOF strategy for Al (III) and pH detection - Ruirui Zhao; Wenjing Lu; Xiaojing Chai; Chuan Dong; Shaomin Shuang; Yujing Guo (Analytica Chimica Acta, 2024)

ERS Mediated by GRP-78/PERK/CHOP Signaling Is Involved in Fluoride-Induced Ameloblast Apoptosis - Li Jinyi; Yang Keyu; Dai Shanshan; He Shuyang; Liu Ruirui; Guo Qingyu; Liu Fei (Biological Trace Element Research, 2024)

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

Paving the way to the future: Mapping historical patterns and future trends of road material stock in Japan - Ruirui Zhang; Naho Yamashita; Zhiwei Liu; Jing Guo; Yuki Hiruta; Hiroaki Shirakawa; Hiroki Tanikawa (Science of The Total Environment, 2023)

Synergistic effect of multi-phase and multi-domain structures induced high energy storage performances under low electric fields in Na0.5Bi0.5TiO3-based lead-free ceramics - Pu Mao; Yongguang Guo; Gang Lu; Qingsong Yan; Ruirui Kang; Ting Wang; Bing Xie; Zhiyong Liu; Lixue Zhang (Chemical Engineering Journal, 2023)

Hyaluronic acid modified oral drug delivery system with mucoadhesiveness and macrophage-targeting for colitis treatment - Ying Zhang; Ruirui Ma; Cuiyu You; Xue Leng; Danyang Wang; Shujing Deng; Binyang He; Ziyang Guo; Zelin Guan; Hengyu Lei; Jie Yu; Qinyuan Zhou; et al. (Carbohydrate Polymers, 2023)

PCNA promotes PRRSV replication by increasing the synthesis of viral genome - Qiumei Wang; Heyou Yi; Yanchen Guo; Yankuo Sun; Zhiqing Yu; Lechen Lu; Ruirui Ye; Ermin Xie; Qianwen Wu; Yingwu Qiu; Weipeng Quan; Guihong Zhang; et al. (Veterinary Microbiology, 2023)

Pyrolysis of Ca/Fe-rich antibiotic fermentation residues into biochars for efficient phosphate removal/recovery from wastewater: Turning hazardous waste to phosphorous fertilizer - Mingdong Zhang; Qinpeng Chen; Ruirui Zhang; Yuting Zhang; Feipeng Wang; Minzhen He; Xiumei Guo; Jian Yang; Xiaoyuan Zhang; Jingli Mu (Science of The Total Environment, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Spatial–temporal dynamics of the built environment toward sustainability: A material stock and flow analysis in Chinese new and old urban areas - Dong Yang; Mengyuan Dang; Jing Guo; Lingwen Sun; Ruirui Zhang; Feng Han; Feng Shi; Qian Liu; Hiroki Tanikawa (Journal of Industrial Ecology, 2023)
The urban built environment has accumulated massive amounts of resources, which is the main “hot spot” of construction materials and energy consumption in cities. To effectively monitor and manage resources use and waste disposal toward sustainability, this study intended to explore different metabolic paths of the urban built environment, as well as strategies for new and old urban areas separately with the help of material stock and flow analysis. Based on snapshots of 2003, 2010, and 2017 and combined with big data, a four‐dimensional geographic information system buildings database of Lixia District in Jinan, China, was compiled for bottom‐up stock modeling. Finally, the environmental impact assessment of the buildings’ demolition and disposal stage was carried out. The results showed that the building material stock was 142.31 Mt in 2017, with an increase of 69% from 2003. The reinforced concrete buildings increased rapidly from 2003 to 2017, especially in new urban areas, which has boosted demand for steel and cement by more than 150% during these 15 years. The material stock of the old urban area tends to be saturated, whereas the new urban area has experienced a rapid expansion with the material inflow four times as large as the material outflow. Potential recycling of waste concrete can reduce the generation of building demolition waste by 50%, save 0.15 km 2 of land occupation, increase raw material substitution by nearly 10 times, and reduce CO 2 emissions by 2.5 times.

Bionic morphological design and interface-free fabrication of halfmoon microrobots with enhanced motion performance - Dong Liu; Dayin Sun; Jiaxin Zhou; Haoran Liu; Ruirui Guo; Bin Wang; Wenjun Ma; Zhenzhong Yang; Yuan Lu (Chemical Engineering Journal, 2023)

What matters most to the material intensity coefficient of buildings? Random forest‐based evidence from China - Ruirui Zhang; Jing Guo; Dong Yang; Hiroaki Shirakawa; Feng Shi; Hiroki Tanikawa (Journal of Industrial Ecology, 2022)
Material intensity coefficient (MIC) is vital for material stock accounting in the field of industrial ecology. However, the categorization of MIC varies across regions especially for buildings that diverge greatly along the history and space aspect, and acquisition of MIC data and building information have always been a challenge in related studies. In this study, the state‐of‐art ensemble model “Random Forest” was developed on Chinese buildings to identify the impact of four building attributes (building structure, construction year, use type, and region) on MIC, and these features’ importance was further assessed by considering variable correlations. The features’ importance and their individual effects on MIC were intuitively revealed by depicting the partial dependence plots. Finally, a set of hierarchical MIC values was estimated by integrating the order of four variables’ importance and a quick MIC calculator was provided. Results showed that building structure is the most influential attribute for MIC, followed by the construction year, use type, and region, successively. The RF‐based MIC values allow researchers to apply it to material stock and flow analysis by choosing a specific building feature(s) in the MIC calculator, which is (are) available in building physical inventory data. This study provides a method that could help researchers locate key influencing variables and give insights into the comparability of MIC research across regions and play an important role in developing urban mining and circular economy strategies.

Nitrogen improves plant cooling capacity under increased environmental temperature - Ruirui Wang; Jixing Zeng; Kehao Chen; Qihui Ding; Qirong Shen; Min Wang; Shiwei Guo (Plant and Soil, 2022)

An extreme gradient boosting technique to estimate TBM penetration rate and prediction platform - Yaxu Wang; Xuechi Gao; Peng Jiang; Xu Guo; Ruirui Wang; Zengda Guan; Lei Chen; Chenxing Xu (Bulletin of Engineering Geology and the Environment, 2022)

Functional community composition has less environmental variability than taxonomic composition in straw-degrading bacteria - Yuanyuan Bao; Zhiying Guo; Ruirui Chen; Meng Wu; Zhongpei Li; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

A mechanical method for predicting TBM penetration rates - Ruirui Wang; Xu Guo; Jianbin Li; Jian Wang; Liujie Jing; Zhengyu Liu; Xinji Xu (Arabian Journal of Geosciences, 2020)

Two key features influencing community assembly processes at regional scale: Initial state and degree of change in environmental conditions - Youzhi Feng; Ruirui Chen; James C. Stegen; Zhiying Guo; Jianwei Zhang; Zhongpei Li; Xiangui Lin (Molecular Ecology, 2018)
Belowground microbial communities strongly influence ecosystem function such that predicting function may rely on understanding ecological processes that assemble communities. Uncertainty remains, however, in what governs the relative contributions of different ecological processes. To help fill this knowledge gap, we test the general hypothesis that both initial state and degree of change in environmental conditions govern the relative contributions of different ecological assembly processes. To do so, we leveraged regional‐scale nutrient and organic matter addition experiments and used soil organic matter (SOM) as a proxy of integrated soil environmental conditions. Consistent with our hypothesis, we found that both the initial amount of SOM and the degree of change in SOM—in response to nutrient addition—influenced the relative contributions of different ecological assembly processes. These influences were most clearly observed at the regional scale, suggesting potential scale dependence. More specifically, nutrient additions homogenized bacterial community composition due to enhanced influences of homogenizing dispersal when SOM content was initially high. In contrast, nutrient additions led to divergence in community composition due to variable selection when initial SOM was low and/or when SOM increased significantly in response to nutrient additions. Our findings indicate important connections among initial conditions, degree of change in environmental variables and microbial community assembly processes that may influence ecosystem processes. These conceptual inferences highlight a need to strengthen connections between ecological theory and biogeochemical modelling.

Facilitation or Competition? The Effects of the Shrub Species Tamarix chinensis on Herbaceous Communities are Dependent on the Successional Stage in an Impacted Coastal Wetland of North China - Ning Du; Pan Wu; Franziska Eller; Dayou Zhou; Jian Liu; Wenhao Gan; Ruirui Yang; Min Dai; Yandong Chen; Renqing Wang; Weihua Guo (Wetlands, 2017)

The relationship between microvasculature in white matter hyperintensities and cognitive function - Jianzhong Sun; Xinfeng Yu; Yerfan Jiaerken; Ruirui Song; Peiyu Huang; Chao Wang; Lixia Yuan; Yingying Mao; Yang Guo; Hualiang Yu; Minming Zhang (Brain Imaging and Behavior, 2017)

Feasibility of human hair follicle-derived mesenchymal stem cells/CultiSpher®-G constructs in regenerative medicine - Pengdong Li; Feilin Liu; Chunling Wu; Wenyue Jiang; Guifang Zhao; Li Liu; Tingting Bai; Li Wang; Yixu Jiang; Lili Guo; Xiaojuan Qi; Junna Kou; et al. (Cell and Tissue Research, 2015)

Molecular diversity of class 2 integrons in antibiotic-resistant gram-negative bacteria found in wastewater environments in China - Ruirui Xia; Ye Ren; Xianhu Guo; Hai Xu (Ecotoxicology, 2013)